Mineral Commodity Summaries 1996 - Significant Events, Trends, And Issues - The Mineral Sector Of The U.S. Economy (The National Institute for Occupational Safety and Health (NIOSH), 1996)
The U.S. economy and, consequently, the demand for minerals grew at more moderate rates in 1995 compared with stronger performances the previous year. Demand for metals such as steel and copper was relatively stable. For example, the decline in steel consumed in motor vehicle manufacturing (reflecting lower vehicle sales) for the first half of 1995 was offset by an increase in steel consumed in construction during the same period. More detailed information on events, trends, and issues in the mineral and material sector Is presented below and in the commodity sections that follow. Overall Performance The value of processed materials of mineral origin produced in the United States during 1995 was estimated to be $395 billion, an increase of almost 10% compared with 1994. The estimated value of U.S. raw nonfuel minerals production in 1995 was $38 billion, about 7% more than in 1994. The value of U.S. minerals production has increased in 30 of the last 35 years.